Kinematics and paleoseismology of the Vernon Fault, Marlborough Fault System, New Zealand: Implications for contractional fault bend deformation, earthquake triggering, and the record of Hikurangi subduction earthquakes. Issue 7 (30th June 2014) - Bartholomew, Timothy D.; Little, Timothy A.; Clark, Kate J.; Van Dissen, Russ; Barnes, Philip M.
Abstract The ~40 km long Vernon Fault, in the Marlborough Fault System of New Zealand, is characterized by dextral slip with subordinate reverse slip and exhibits abrupt variations in strike of up to 90°. Onshore fieldwork, paleoseismic trenching, and offshore high‐frequency seismic reflection data are integrated together to identify the kinematics and paleoseismic history of three sections of the fault: (1) the NNE striking Vernon Hills section which branches off from the Awatere Fault; (2) the NE striking Big Lagoon section which borders Big Lagoon to the south and extends ~9 km offshore to the east; and (3) the E‐W striking Wairau Basin section, which is entirely submarine. The Vernon Fault can be shown to have a dextral slip rate of 0.8–4.9 mm/yr with a preferred estimate of 0.9 mm/yr (on the Big Lagoon section). We infer that a further unrecognized 3–4 mm/yr of dextral slip has been accommodated off fault as a result of accumulated slip on small and/or blind reverse faults adjacent to a 6 km wide restraining bend in the main fault. The onshore and offshore paleoseismic records are in good agreement. These indicate three to five events at eight sites and a mean recurrence interval of 3.9 ± 1.2 ka over the past ~16 kyr, with the last event taking place at ~3.3 ka. Earthquakes on the Vernon Fault are responsible for <25% of the Holocene subsidence rate of Big Lagoon over the last ~13 ka. Most of the subsidence of this lagoon has been the result of surface deformation related with southern Hikurangi megathrust earthquakes.